2023
DOI: 10.3389/fimmu.2023.1265406
|View full text |Cite
|
Sign up to set email alerts
|

Risk of head and neck cancer in relation to blood inflammatory biomarkers in the Swedish AMORIS cohort

Yanping Yang,
Yushan Liang,
Fatemeh Sadeghi
et al.

Abstract: BackgroundInflammation is critically involved in the development of human cancer, and blood inflammatory biomarkers have been proposed to indicate the risk of different cancer types.MethodsUsing the Swedish Apolipoprotein-Related Mortality Risk (AMORIS) Cohort (N=812,073), we first performed a time-to-event analysis to evaluate the association of the baseline level of 12 blood inflammatory biomarkers measured during 1985-1996 with the subsequent risk of head and neck cancer (HNC) identified through the nationw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 73 publications
1
0
0
Order By: Relevance
“…Moreover, previous studies demonstrated that activation of the immune system and chronic inflammation were involved in the occurrence and development of these diseases ( 24 ). LMR has been reported to be associated not only with an increased risk of death from multiple malignant diseases, but also with a poor prognosis for coronary artery disease ( 25 27 ).. In our study, compared with participants of the higher LMR, the lower LMR had higher levels of neutrophil and hs-CRP and a higher prevalence of metabolic disorders such as diabetes, heart failure and coronary artery disease.…”
Section: Discussionsupporting
confidence: 45%
“…Moreover, previous studies demonstrated that activation of the immune system and chronic inflammation were involved in the occurrence and development of these diseases ( 24 ). LMR has been reported to be associated not only with an increased risk of death from multiple malignant diseases, but also with a poor prognosis for coronary artery disease ( 25 27 ).. In our study, compared with participants of the higher LMR, the lower LMR had higher levels of neutrophil and hs-CRP and a higher prevalence of metabolic disorders such as diabetes, heart failure and coronary artery disease.…”
Section: Discussionsupporting
confidence: 45%